Project of deuteron accelerator based neutron source for rib production - Avilov, M.S.; Gubin, K.V.; Kot, N.Kh.; Lebedev, N.N.; Logatchev, P.V.; Martyshkin, P.V.; Morozov, S.N.; Pivovarov, I.L.; Shiyankov, S.V.; Starostenko, A.A.; Tecchio, L. (Вопросы атомной науки и техники, 2001)
The project of a high-intense neutron source for the SPES project in LNL, Legnaro, Italy [1] is developed. The source is based on the rotating carbon target. The target is bombarded by the deuteron beam with energy 20 MeV, diameter 1 cm, average power 100 kW. The target is cooled by its thermal radiation, and its temperature can reach 1800ºC. It is shown that high density graphite can be used as a material for neutron production. The source can produce up to 10¹⁴ neutrons per second with energy within few MeV - few dozens MeV range, its lifetime is around few thousand hours.